Pekerja Ekonomi Gig: Pengalaman Kerja Pengemudi Ojek Online Maxim dan Grab di Wilayah Timur Indonesia - I Putu Yoga Bumi Pradana (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
This study aims to examine the work experience of online Ojek drivers in Kupang City who use the Maxim and Grab platforms. This research is motivated by the rapid development of online ojek services in Indonesia, including in Kupang City, as well as its important role in providing new economic opportunities. This research uses a qualitative approach with phenomenological methods to explore the subjective experiences of the drivers. In-depth interview techniques and participatory observation were used to collect data from 22 informants consisting of Maxim and Grab drivers. The results showed significant differences between the drivers' work experiences on the two platforms. Grab drivers prefer the strict Standard Operating Procedures (SOPs) that provide a sense of security, while Maxim drivers appreciate the flexibility of working hours offered. The main challenges faced by drivers include digital map inaccuracies, sudden order cancellations, accident risks, and poor road conditions. The rating system plays an important role in determining a driver's income, with high ratings increasing the number of orders. This research makes an important contribution to the literature by providing an in-depth comparative analysis of the work experience of online ojek drivers in a medium-sized city like Kupang. The findings also offer practical recommendations for online Ojek companies to improve driver welfare and provide useful data for policymakers in formulating regulations that support the welfare of online Ojek drivers.